The Effectiveness of the Power of Two Method on Mathematical Problem Solving Ability of Class XI MA Attarbiah Islamiah Kolaka Students - Darsono; Fitriyani Hali; Tahir (Arden Jaya Publisher, 2021)
This research is an experimental research, with the aim to find out: (1) how the students' mathematical problem solving ability before the application of the Power of Two method; (2) how is the students' mathematical problem solving ability after the application of the Power of Two method; (3) whether the Power of Two method is effective on students' mathematical problem solving abilities. The population in this study were all students of class XI MA Attarbiah Islamiah Kolaka in the 2020-2021 school year which consisted of 1 class with a total of 30 students. Sampling is done by using a census or total sampling. Sampling is done by using all the population. The analysis used is descriptive analysis and inferential analysis. Furthermore, the results are based on hypothesis testing: a statistical t-test (one sample t-test) was performed. It was obtained that tcount = -8.53 with ttable = -1.67. Accept H0 if -1.67≤ tcount≤ 1.67 because tcount = -8.53 is outside the H0 acceptance interval, then H0 is rejected and H1 is accepted. Thus there is a significant difference between students' mathematical problem solving ability scores before using the Power of Two method and after using the Power of Two method.